The Influence Of Muslim Friendly Tourism On The Satisfaction Of Tourists Visiting The Tourist Attraction Of Air Manis Beach In Padang City - Abdiska, Debi; Kamarni, Neng; N., Zulkifli (Jurnal Ekonomi, 2024)
Muslim Friendly Tourism is a fast-growing tourism segment, providing facilities, services and management according to sharia principles. This concept provides satisfaction, especially for Muslim tourists, but can still be enjoyed by non-Muslim tourists. This research aims to determine the influence of Muslim Friendly Tourism on tourist satisfaction at Air Manis Beach, Padang City. The type of research is quantitative descriptive with a survey approach. The data used is primary data from tourists who visit the Air Manis Beach tourist attraction, Padang City. Data was collected through incidental sampling with a sample size of 100 tourists. Data analysis using simple regression. The results of this research show that the Muslim Friendly Tourism variable has a significant effect on the satisfaction variable of tourists who visit the Air Manis Beach tourist attraction, Padang City. Thus, the implementation of the policy is expected for the management of the Air Manis Beach tourist attraction in Padang City to improve tourist facilities and services in accordance with Islamic law.